Students' peer feedback engagements in online English courses facilitated by a social network in Thailand - Budi Waluyo; Benjamin Panmei (OmniaScience, 2024)
Despite the extensive research on peer feedback in recent years, there is limited understanding of how students engage in peer feedback activities within online English courses and their expectations during these activities. Hence, using a sequential explanatory mixed methods design with a phenomenological approach, this study integrated online peer feedback (OPF) activities into a 12-week online English writing course involving 30 second-year students (16.7% male, 83.3% female) facilitated by a Facebook group. Data were collected through survey questionnaires, written reflections, and task scores. Descriptive statistics and bivariate correlations were used to analyze the quantitative data, while thematic analysis was employed for the qualitative data. Three findings emerged: 1) EFL students exhibited positive engagements in OPF activities, 2) Students' engagements were not significantly correlated with their writing outcomes, and 3) Students provided recommendations for improving the quality and quantity of feedback, incorporating teacher feedback and guidance, and enhancing the overall process and experience. Based on these findings, integrating OPF activities into the academic curriculum is suggested, with a focus on providing guidance to students for delivering descriptive and constructive feedback, offering scaffolding to enhance their comprehension, and writing skills, and addressing concerns related to language proficiency and grammar.